Peran Kepribadian Wirausaha dan Inovasi Wirausaha dalam Meningkatkan Kinerja Manajerial - Sri Rustiyaningsih; F. Anif Farida; Veronika Agustini Srimulyani (Fakultas Ekonomi Universitas Kadiri, 2024)
A tough and innovative entrepreneur is the basic capital to survive and win business competition. This study aims to examine entrepreneurial innovation as a mediation effect of entrepreneurial personality on managerial performance. The research sample is SMEs in the city and district of Madiun which have been established for 5 years. Hypothesis testing with path analysis and Sobel test. The results of the study found that entrepreneurial personality influences managerial performance. Entrepreneurial personality influences entrepreneurial innovation. However, developer innovation influences managerial performance at a significant level of 0.1. Entrepreneurial innovation is not proven as a mediation between entrepreneurial personality and managerial performance. Implications for owners and/or managers of SMEs to improve their entrepreneurial personality so they can seize business opportunities and develop a competitive advantage.